FACTORS AFFECTING TAX COMPLIANCE AMONG COOPERATIVES TAXPAYERS IN MALAYSIA - Sri Atikah Binti Md Samuji; Rani Diana Binti Othman; Zubaidah Ismail (International Journal of Accounting, Finance and Business, 2022)
Like other tax administrators in the world, Inland Revenue Board of Malaysia (IRBM), has continuously focuses on tax avoidance and tax non-compliance problem which affect the nation’s tax collection. Recently, increased attention is given to cooperatives taxpayers as its contribution towards Malaysian’s GDP is expected to increase up to 5% in 2025 compared to 3%-4% in year 2021. However, despite of 14,427 cooperatives registered with Commission of Malaysia (SKM) in 2018, only 3,534 registered as taxpayer under Form CI category. To understand this phenomenon, a study is conducted to understand the effect of tax knowledge, tax awareness and compliance cost toward compliance behavior among cooperatives taxpayer in the southern region of Malaysia. Adopting Attribution theory, this study is expected to shed some light on the issue and provides suggestion to improve the role of SKM and IRBM in ensuring higher tax compliance among Malaysian’s cooperatives.